Comparative evaluation of sticky bone with guided tissue regeneration and platelet-rich fibrin membranes in healing of apicomarginal defects with periapical pathology: An in-vivo study - D. Das; P. Mondal; K. K. Saha; S. Das; D. Karmakar; A. Bhagawati (Эндодонтия Today, 2024)
AIM. The objective of this study is to comparatively evaluate the effectiveness of sticky bone alone, sticky bone with a PRF membrane, as well as sticky bone having a GTR membrane in healing apicomarginal defects.MATERIALS AND METHODS. Twenty-seven patients with apicomarginal defects were randomly divided into three groups: Group I (sticky bone alone), Group II (sticky bone with GTR membrane), and Group III (sticky bone with PRF membrane). Clinical and radiographic assessments, including probing depth, bone density, and lesion size, were conducted. Statistical analyses included paired t-tests and ANOVA with a remarkable level of p < 0.05.RESULTS. Notable improvements in all parameters were observed across groups (p < 0.05). Group III showed the most notable reductions in probing depth and lesion size and the highest increase in bone density. Group II exhibited moderate improvements, while Group I had the least favorable outcomes.CONCLUSION. Combining sticky bone with PRF or GTR enhances bone healing in apicomarginal defects, with PRF yielding the best results.